2017
DOI: 10.3758/s13421-017-0719-y
|View full text |Cite|
|
Sign up to set email alerts
|

Serial reconstruction of order and serial recall in verbal short-term memory

Abstract: We carried out a series of experiments on verbal short-term memory for lists of words. In the first experiment, participants were tested via immediate serial recall, and word frequency and list set size were manipulated. With closed lists, the same set of items was repeatedly sampled, and with open lists, no item was presented more than once. In serial recall, effects of word frequency and set size were found. When a serial reconstruction-of-order task was used, in a second experiment, robust effects of word f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 32 publications
(60 reference statements)
2
21
0
Order By: Relevance
“…The important results from the analysis of the accuracy data are that a word frequency effect was observed and that it did not interact with either set size or experiment half. The lack of a set size effect replicated Experiment 1 of Quinlan et al (2017) but differed from the significant set size effect reported by Roodenrys and Quinlan (2000). It is not clear what the key difference is between the studies.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…The important results from the analysis of the accuracy data are that a word frequency effect was observed and that it did not interact with either set size or experiment half. The lack of a set size effect replicated Experiment 1 of Quinlan et al (2017) but differed from the significant set size effect reported by Roodenrys and Quinlan (2000). It is not clear what the key difference is between the studies.…”
Section: Resultsmentioning
confidence: 60%
“…Experiment 3 was designed to see whether the frequency effect that is observed when a large open set is used would also be observed when a small closed set was used, as had previously been reported by both Roodenrys and Quinlan (2000) and Quinlan et al (2017). Experiment 3, then, was identical to Experiment 1, except that word frequency was manipulated instead of concreteness.…”
Section: Methodsmentioning
confidence: 99%
“…On this basis they proposed that SMG plays a crucial role in memory for serial order. We did not find an increase in item order errors with SMG stimulation but when the phonological form of items are well-learned or a task uses a restricted set of items (like the number words 1-9), the task demands focus on the retention of whole items in order (Quinlan, Roodenrys, & Miller, 2017; Roodenrys & Quinlan, 2000;Saint-Aubin & Poirier, 2000). In contrast, for unfamiliar items (like nonwords), ordering mechanisms are necessary to maintain constituent phonemes in sequence, and consequently, disruption of ordering mechanisms gives rise to item errors of the form we observed (Jefferies, Frankish, et al, 2006a, 2006bJefferies, Lambon Ralph, & Baddeley, 2004;Page, Madge, Cumming, & Norris, 2007;Savill, Ashton, et al, 2015).…”
Section: Role Of Left Anterior Supramarginal Gyrusmentioning
confidence: 62%
“…Redintegration is effectively selection of a recall option from a set of candidates according to the relative strength of evidence from memory that each of them receives. In support, a direct comparison of both methods also shows that two experimental variablesserial position and word frequency -affect serial-order reconstruction and serial recall of words in the same way (Quinlan, Roodenrys, & Miller, 2017) Taking a broader perspective, the different labels we use to describe the multitude of procedures for testing (working) memory -such as "recall", "recognition", or "reconstruction" -do not map well onto the different decision processes we demand through these procedures. Many methods described by these labels share the requirement to select one element from a set of candidates.…”
Section: Varieties Of Testing Memorymentioning
confidence: 98%
“…The normal distribution is not meant to describe the true distribution of parameters but to function as a convenient approximation of the true distribution. We applied the 64 model versions to the data from each experiment using JAGS 4.2 (Plummer, 2016) for running the MCMC samples, together with the R2jags package (Su, 2015) in R (R_Core_Team, 2017). Model comparison was based on the WAIC information criterion (Watanabe, 2010), which is suited for hierarchical models and has better statistical properties than the more often used DIC (Gelman, Hwang, & Vehtari, 2014).…”
Section: Bayesian Hierarchical Implementationmentioning
confidence: 99%